Reason, purpose and members : a critical discourse analysis of a Swedish agricultural cooperative - Björklund, Magne (SLU/Dept. of Urban and Rural Development, 2019)
The declining number of Swedish farmers and the consolidation of agricultural land has been raised as a future risk for the food security of Sweden. As the Swe-dish agricultural historically has been characterized by strong agricultural coop-eratives, the cooperative movement is of interest to analyze in relation to this trend of decline. In this thesis I critically study a Swedish agricultural coopera-tive, Lantmännen. Specifically, I study how the purpose of the cooperative has changed over time in relation to agricultural policy. In order to explore how the purpose of Lantmännen has changed, I have utilized the method of Political Dis-course Analysis. I have by discourse analysis examined the goals and values, ex-pressed in the internal discussion of the Lantmännen cooperative, through proto-cols of the administrative board and statements of the president of the organiza-tion. The study stretches between 1985 and 2009, a period when the Swedish and later European agricultural policies changed fundamentally. The study shows how the goals and values changes in the argumentation of Lantmännen during the period, as a reaction to the changed agricultural policy. The changes in goals and values, in Lantmännen, were to such an extent, that the purpose of that organiza-tion had to be reformulated, which it effectively was during the 2000’s. In 1985 discussions in Lantmännen’s administrative board was characterized by a multi-plicity values to address, concerning solidarity and societal interest, when acting in respect to the changing agricultural policies. In 2009 the president of Lantmän-nen praised, that the same organization had realized its vision of becoming a thin-ner, clearer and profit producing; reflecting a transition from a cooperative iden-tity into an investor-owned firm’s (IOF). In the early material studied, the study shows how member interest (in its complexity) was the key goal in shaping deci-sion making of Lantmännen; in the later material, it is revealed, member interest was reformulated to simulate the interest of an investor. Thereby, profits and mar-ket shares could take the position as fundamental goals of decision making.